1983
DOI: 10.1002/1097-0142(19830315)51:6<1138::aid-cncr2820510627>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of growth patterns of early gastric carcinoma determined by cytophotometric0 DNA analysis

Abstract: Cell nuclear DNA content was microspectrophotometrically measured in 60 cases of early and six of advanced gastric carcinoma. DNA distribution pattern was classified into Types I, II and III, according to the degree of dispersion on the DNA histogram. Five of 6 cases of the advanced carcinomas were Type III. In early carcinoma, the majority of Super (superfically spreading) type were Type II, while all of Pen A (expansively penetrating growth) type were Type III. In Pen B (infiltratively penetrating growth)typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…In contrast, the Pen-A type tumor is characterized by dominant elevated lesions and a relatively high incidence of liver metastasis. We have investigated DNA ploidy 21 and p53 abnormality 22 in these different growth types of early gastric carcinoma. The Super type has diploidy and normal p53, whereas the Pen-A type has aneuploidy and abnormal p53.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Pen-A type tumor is characterized by dominant elevated lesions and a relatively high incidence of liver metastasis. We have investigated DNA ploidy 21 and p53 abnormality 22 in these different growth types of early gastric carcinoma. The Super type has diploidy and normal p53, whereas the Pen-A type has aneuploidy and abnormal p53.…”
Section: Discussionmentioning
confidence: 99%
“…The biological characteristics of highly malignant tumours have been studied by DNA analyses [18,22], and estimation of DNA abnormalities by means of flow cytometry or cytofluorometry may substantially contribute to knowledge of the biological characteristics of gastric cancer. Takai et al [57] reported that aneuploid tumours had significantly higher levels of uPA content than diploid ones.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, subtle differences, difficult to detect, might exist between the biological characteristics of neoplastic cells. Quantitative pathology (Tosi et al, 1984(Tosi et al, , 1986(Tosi et al, , 1987, image processing analysis (Schipper et al, 1987) and interpretation of DNA histograms of tumor cells by means of static (Inokuchi et al, 1983;Korenaga et al, 1985;Kamegawa et al, 1986) and flow cytometry (Fallenius et al, 1987) are among the means employed in the attempt to reveal such differences. In particular, DNA histograms by flow cytometry of routine histologically processed tissue have been analyzed in order to detect aneuploid patterns, which seem to be correlated with poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%